PELATIHAN PEMANFAATAN LIMBAH SAYURAN RUMAH TANGGA MENJADI SISTEM REGROW DI DESA WONOPRINGGRO KECAMATAN WONOPRINGGO - Fifin Fauziyah; Dinda Himatul Alya; Anandya Hadiprasetya; Deril Eka Dava Nugraha; Muhammad Taqwa; Immanuel Nugroho; Sania Rizqina; Dimas Rizqi Nugroho (Perwira Journal of Community Development, 2026)
Wonopringgo Village is located in Wonopringgo Subdistrict, Pekalongan Regency, and has a fairly high population density, so this village faces complex challenges related to population dynamics, one of which is related to waste. This is in line with the high level of domestic activity of residents, which has a direct impact on the increase in the volume of household waste produced every day. Waste management in Wonopringgo Village is still ineffective. Residents often mix organic waste with plastic waste, causing unpleasant odors. Instead of being discarded, vegetable scraps can be reused for planting. The roots of certain vegetables still have the potential to grow into new plants if replanted, a process known as regrowth. Therefore, training on the utilization of household vegetable waste into a regrowth system was held with the aim of providing the community with the skills to manage vegetable waste into a regrowth system that supports gardening in home yards and maintains food security. This training was intended for the Wonopringgo Village PKK group. The methods used included preparation, dissemination, practice, discussion, and evaluation. The evaluation was conducted by collecting data obtained through assessment instruments in the form of pre-test and post-test forms. The evaluation results showed a significant increase, with all participants expressing interest in applying the regrow technique after the training.